Samaritan Zatoichi Based on a Short Story by Kan Shimozawa - Misumi, Kenji; Morita, Fujio; Katsu, Shintaro; Mita, Yoshiko; Satô, Makoto (Criterion, 2019)
Hired by a yakuza boss to eliminate an accused debtor, Zatoichi fulfills his task, only to witness the victim's sister paying the owed amount minutes later. When the crime lord tries to possess the woman along with the cash, the blind swordsman wrestles with the injustice he has caused, and vows to protect the young lady at all costs. [www.criterion.com]
Keywords: Blu-Ray-Disc